Legal Vacuum: Conflicts of Interest for Public Accountants and Practicing Accountants in Indonesia - Hidayatullah; Agus Triono; FX Sumarja (Formosa Journal of Multidisciplinary Research, 2022)
Cases that arise related to financial reports audited by public accountants cannot be separated from how a public accountant provides his services. The overlap between the services provided by Public Accountants and Practicing Accountants can lead to conflicts of interest, efforts to minimize conflicts of interest do not yet have comprehensive regulations in place to anticipate since applying for permits to anticipate conflicts of interest, currently new conflict of interest limits are from the side of only one public accountant, this legal vacuum needs to be it becomes a thought for policy makers to make regulations that Public Accountants and Practicing Accountants must choose one if they want to apply for a license, they are prohibited from applying for both permits at once but choose only one permit